2019
DOI: 10.1186/s12864-019-6206-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals a novel genetic organization of the sad cluster in the sulfonamide-degrader ‘Candidatus Leucobacter sulfamidivorax’ strain GP

Abstract: BackgroundMicrobial communities recurrently establish metabolic associations resulting in increased fitness and ability to perform complex tasks, such as xenobiotic degradation. In a previous study, we have described a sulfonamide-degrading consortium consisting of a novel low-abundant actinobacterium, named strain GP, and Achromobacter denitrificans PR1. However, we found that strain GP was unable to grow independently and could not be further purified.ResultsPrevious studies suggested that strain GP might re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 143 publications
(213 reference statements)
0
2
1
Order By: Relevance
“…Although previous studies have indicated that sadA is potentially mobile in other antibiotroph strains (Ricken et al, 2017;Reis et al, 2019), our results did not show any increase in the sadA/groL ratio (data not shown), suggesting an absence of horizontal gene transfer. This is consistent with the chromosomic localization of sadA, which makes its mobility via a horizontal gene transfer event unlikely (whole genome sequencing of Microbacterium sp.…”
Section: The Presence Of Genetic Potential For Antibiotrophy In Soil Does Not Guarantee Its Expressioncontrasting
confidence: 94%
“…Although previous studies have indicated that sadA is potentially mobile in other antibiotroph strains (Ricken et al, 2017;Reis et al, 2019), our results did not show any increase in the sadA/groL ratio (data not shown), suggesting an absence of horizontal gene transfer. This is consistent with the chromosomic localization of sadA, which makes its mobility via a horizontal gene transfer event unlikely (whole genome sequencing of Microbacterium sp.…”
Section: The Presence Of Genetic Potential For Antibiotrophy In Soil Does Not Guarantee Its Expressioncontrasting
confidence: 94%
“…For example, SadA had a wider pocket than its homolog XiaF, and Leucobacter strain GP containing SadA showed better sulfonamide removal than Microbacterium sp. BR1 containing XiaF 76 .…”
Section: Resultsmentioning
confidence: 99%
“…This strain was actually the first bacterium for which the genes and enzymes involved in the use of an antibiotic as a carbon and energy source had been characterized. The sad cluster is flanked by sequences encoding for mobile genetic elements (Ricken et al, 2017), as was also the case for Candidatus Leucobacter sulfamidivorax, where multiple copies of sadA were found to be flanked by single IS1380 family transposases (Reis et al, 2019). Moreover, the sulfonamide-resistant gene sul1 is commonly found in class 1 integrons and therefore known to be easily disseminated (Gillings, 2014).…”
Section: Introductionmentioning
confidence: 86%